Production service system enabled by cloud-based smart resource hierarchy for a highly dynamic synchronized production process. (October 2019) - Zhang, Kai; Wan, Ming; Qu, Ting; Jiang, Hongfei; Li, Peize; Chen, Zefeng; Xiang, Jinjie; He, Xiaodong; Li, Congdong; Huang, George Q.
Highlights: Analyze the resource management needs from the aspect of industrial development. Proposed a new mode of S-PnSS toward the contemporary production development stage. PnSS-CSRH gives synchronization soft & smart hardware-based solutions in PnSS mode. Abstract: The rapidly changing market demands entail a modern production system to cope with ever more diversified production orders. Not only the parameters and flow of the production process, sometimes the production resources and the corresponding application systems which make production decision and control even need to be reconfigurable. Due to the inability to provide dynamically reconfigurable manufacturing resources, systems and application systems, enterprises have to sacrifice profits to narrow their business scope or take risks to purchase a large number of production resources. In any case, it has brought operational burden to enterprises. This paper systematically analyses the production management requirements of a large-scale production system in terms of both hardware (production equipment) and software (application system) which is oriented to dynamic production demands, and then proposes a production service system enabled by cloud-based smart resource hierarchy (PnSS-CSRH). The platform is based on an open resource management system and inherits the general cloud structure and the AUTOM framework. PnSS-CSRH provides industrial users with integrated and synchronization services for the software and hardware resources involved in the production process in the PnSS mode. Using the integrated service mode, PnSS-CSRH not only helps resource providers to increase the frequency of resource leases, provides customers with targeted and systemic hardware and software overall solutions, and increases the platform usage rate, which brings more benefits to the stakeholders of PnSS-CSRH. At last, the PnSS-CSRH is used to provide services to the case company to validate the effectiveness.